Analisis Filsafat Stoikisme Pada Tokoh Andy Dufresne dalam Film The Shawshank Redemption - Rosa Lamria Mardiana Simbolon; Syihabuddin Syihabuddin (Departement of Mathematics Education, 2024)
This research aims to analyze the influence of Stoicism values ​​on the development of moral character, dynamics of social relationships, and acceptance of destiny in the film